Depredation in gillnets operated along the south-west coast of India - Chinnadurai, S.; Jha, Paras Nath; Renjith, R. K.; Remesan, M. P.; Thomas, Saly N.; Baiju, M. V. (Indian Journal of Fisheries, 2018)
Experimental gillnet (polyamide, 210 dÃ—9Ã—3 with 140 mm mesh size) fishing was conducted onboard FV Sagar Harita (LOA19.5 m) during September, 2016. Out of six sets deployed, three incidents of depredation, possibly by puffer fish were observed, when 41.5, 33.7 and 40% of the catch was lost. Depredation could be prevented effectively by frequent monitoring of the deployed gillnets at shorter intervals. Studies on depredation with special reference to soaking time, hauling speed, seasonal variation and location of fishing grounds are needed in view of the economic losses incurred.